Athermal migration of vacancies in iron and copper induced by electron irradiation. Issue 9 (24th March 2017) - Satoh, Y.; Sohtome, T.; Abe, H.; Matsukawa, Y.; Kano, S.
Abstract: Irradiation with high-energy particles induces athermal migration of point defects, which affects defect reactions at low temperatures where thermal migration is negligible. We conducted molecular dynamics simulations of vacancy migration in iron and copper driven by recoil energies under electron irradiation in a high-voltage electron microscope. Minimum kinetic energy required for migration was about 0.8 and 1.0 eV in iron and copper at 20 K, which was slightly higher than the activation energy for vacancy migration. Around the minimum energy, the migration succeeded only when a first nearest neighbour (1NN) atom received the kinetic energy towards the vacancy. The migration was induced by higher kinetic energies even with larger deflection angles. Above several electron-volts and a few 10s of electron-volts, vacancies migrated directly to 2NN and 3NN sites, respectively. Vacancy migration had complicated directional dependence at higher kinetic energies through multiple collisions and replacement of atoms. The probability of vacancy migration increased with the kinetic energy and remained around 0.3–0.5 jumps per recoil event for 20–100 eV. At higher temperatures, thermal energies slightly increased the probability for kinetic energies less than 1.5 eV. The cross section of vacancy migration was 3040 and 2940 barns for 1NN atoms in iron and copper under irradiation with 1.25 MV electrons at 20 K: the previous result was overestimated by about five times.